Dos Mundos Rural Mexican Americans, Another America - Baker, Richard (Utah State University Press, 1995)
Mexican Americans make up the largest minority in Idaho, yet they seemingly live in a different world from the dominant Anglo population, and because of pervasive stereotypes and exclusive policies, their participation in the community's social, economic, and political life is continually impeded. This unique ethnographic study of a small Idaho community with a large Hispanic population examines many dimensions of the impact race relations have on everyday life for rural Mexican Americans.